Absorption Laws (Boolean Algebras)

From ProofWiki
Jump to: navigation, search

This proof is about the absorption laws as they apply to Boolean algebras. For other uses, see Absorption Laws.


Let $\left({S, \vee, \wedge}\right)$ be a Boolean algebra, defined as in Definition 1.

Then for all $a, b \in S$:

$a = a \vee \left({a \wedge b}\right)$
$a = a \wedge \left({a \vee b}\right)$

That is, $\vee$ absorbs $\wedge$, and $\wedge$ absorbs $\vee$.


Let $a, b \in S$.


\(\displaystyle a \vee \left({a \wedge b}\right)\) \(=\) \(\displaystyle \left({a \wedge \top}\right) \vee \left({a \wedge b}\right)\) $\quad$ Boolean Algebra: Axiom $(BA_1 \ 3)$: $\top$ is the identity for $\wedge$ $\quad$
\(\displaystyle \) \(=\) \(\displaystyle a \wedge \left({\top \vee b}\right)\) $\quad$ Boolean Algebra: Axiom $(BA_1 \ 2)$: $\wedge$ distributes over $\vee$ $\quad$
\(\displaystyle \) \(=\) \(\displaystyle a \wedge \top\) $\quad$ Identities of Boolean Algebra also Zeroes $\quad$
\(\displaystyle \) \(=\) \(\displaystyle a\) $\quad$ Boolean Algebra: Axiom $(BA_1 \ 3)$ $\top$ is the identity for $\wedge$ $\quad$

as desired.


The result:

$a = a \wedge \left({a \vee b}\right)$

follows from the Duality Principle.